Coefficient of friction equation for gears based on a modified Hersey parameter. (September 2016) - Fernandes, Carlos M.C.G.; Martins, Ramiro C.; Seabra, Jorge H.O.
Abstract: The present work is first of all a bibliographic revision about the coefficient of friction equations for gears. The available expressions were compared and used to predict experimental results trying to draw an overview about the main advantages and disadvantages of each method. A load sharing function to predict the coefficient of friction was developed based on a modified Hersey parameter. A coefficient of friction equation is then proposed trying to improve the existing methods, including the influence of the oil pressure–viscosity parameter, on the coefficient of friction. The new equation correlates very well with the experimental results. Abstract : Highlights: Different coefficients of friction equations for gears were compared. A new coefficient of friction equation is proposed to improve the existent methods. New equation includes the influence of the oil pressure–viscosity. New equation is based on a modified Hersey parameter.